Measurement of oxygen concentration delivered via nasal cannulae by tracheal sampling. Issue 4 (24th March 2014) - O'Reilly Nugent, Andrew; Kelly, Paul T.; Stanton, Josh; Swanney, Maureen P.; Graham, Bruce; Beckert, Lutz
Abstract Background and objective Oxygen is used in many clinical scenarios, however the variable performance of nasal cannulae makes determining the precise fraction of inspired oxygen (FiO2) difficult. We developed a novel method for measurement of the tracheal FiO2 using a catheter placed via bronchoscopy. We investigate the effects of oxygen delivery, respiratory rate, mouth position and estimated minute ventilation (VE) on the FiO2 delivered by nasal cannulae. Methods The catheter was placed in 20 subjects. Tracheal gas concentrations were analysed during six 5‐min treatments controlling for oxygen delivery rate, respiratory rate and mouth position. Ventilation was monitored with respiratory inductive plethysmography (RIP). The FiO2 delivered by nasal cannulae was compared between treatments, and we investigated the relationships among the FiO2, alveolar partial pressure of oxygen (PAO2) and VE. Results The FiO2 increased by 0.038/L/min of oxygen. Respiratory rate had a significant effect on the FiO2. A normal respiratory rate of 15 breaths/min and oxygen supplementation via nasal cannula at 2 L/min resulted in an FiO2 of 0.296; however, FiO2 decreased by 0.012 at 20 breaths/min and 0.004 at 10 breaths/min. The mean FiO2 decreased by 0.024 with the mouth open. The FiO2 and PAO2 were observed to decrease with increasing VE. Conclusions Continuous measurement of the FiO2 using a transtracheal catheter provides detailed insight into inspiratory changes of the FiO2 delivered by nasal cannulae. Our study confirms that respiratory rate, VE and mouth position significantly influence the inspired oxygen concentration. These parameters should be accounted for when prescribing oxygen.